THE INFLUENCE OF COLORING PICTURE THROUGH FINE MOTOR DEVELOPMENT ON CHILDREN AGE 4-5 YEARS GROUP: PENGARUH MEWARNAI GAMBAR TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK USIA 4-5 TAHUN KELOMPOK A DI PAUD PUSPA BANGSA KOTA BOGOR - Fitria Hari Wibawati (Wijaya Husada, 2018)
According to the World Health Organization (WHO) reported that 2-25% of children preschool age suffering minor brain dysfunction, included smooth motion development problems, in Indonesia around 16% of children experience problems the development of smooth motion. Smooth motion development involves certain body parts done by small muscles. How to stimulate fine motor in children has a very big function that is to improve the mevement of subtle activities such as writing, drawing and typing. The impact will occur when a child in smooth motion development that can lead to cerebral palcy. To determine the influence of coloring picture toward smooth motion development in children age 4-5 years group A Puspa Bangsa Kindergarten Bogor. The type of research is pre-experimental was conducted in Puspa Bangsa Kindergarten Bogor on 30th November until 1st December 2016 and the respondents are 30 children with age 4-5 years by using Total Sampling technique. To collect the data of this research, the researcher use using observational sheet. The Knowledgeable of univariat analysis before being given coloring treatment are 50% of children in the category of underdeveloped and after being given coloring treatment are 50% of children in the category of developing according to expectations. The bivariate analysis using Shapiro Wilk normality test using the results of 0,000 < 0,05 means thatthe data are not normality distributed,then to test hypothesis using Willcoxon test with p value 0,000<0,05 it means Ho rejected and Ha accepted. Knowledgeble of smooth motion development of 30 respondents (50%) fall into the category of underdeveloped with a mean value of 1,87 and a standard deviation of 0,937. The Knowleadable of smooth motion development of 30 respondents (50%) fall into the category growing as expected with a mean value of 2,90 and a standard deviation of 0,712.There is Influence of Coloring Pictures Toward Smooth Motion Development In Children Age 4-5 Years Group A in Puspa Bangsa Kindergarten Bogor.